La régulation de la concurrence en France et en Tunisie à la lumière du droit économique européen - Bhouri, Habiba (Université Jean Moulin Lyon 3, 2023)
En France, la décision d'ouvrir le marché à la concurrence et à l'économie de marché a été prise de manière autonome en tant que décision politique nationale, marquée par la réforme des monopoles publics. En revanche, en Tunisie, le processus de libéralisation a été mis en place sous la pression des principales institutions financières internationales en réponse aux défis économiques auxquels le pays était confronté. La Tunisie a été contrainte d'adopter certaines directives visant à accroître sa compétitivité sur les marchés mondiaux, ce qui a conduit à la création de mécanismes de régulation plus flexibles et transparents. L'analyse du cas tunisien est d'un intérêt particulier, car elle met en évidence l'influence juridique exercée sur certains pays lorsqu'ils se préparent à rejoindre l'Union européenne ou à établir des partenariats avec elle. Cette évolution peut être examinée à travers d’une part, l'analyse du cadre juridique, et d’autre part, le cadre institutionnel et opérationnel de la régulation de la concurrence.
Keywords: Anti-Competitive practices; Comparative law; Competencia; Competition law; Concurrence; Concurrence (droit); Contrôle des concentrations; Droit comparé; Droit français; Droit tunisien; Droit économique européen; European economic law; France; French law; Merger control; Pratique anticoncurrentielle; Regulation; Régulation; Tunisian law; Tunisie; Études comparatives

Le juge du droit de la concurrence - Castryck Fernandez, Emmanuel (Université de Perpignan, 2023)
Un juge en droit de la concurrence est un juge qui est chargé de veiller à ce que les lois sur la concurrence soient respectées. La difficulté est que cette définition peut s’appliquer autant à un juge qu’à une autorité. En effet, le choix de ne pas adapter l’appareil juridictionnel pour une juridiction spécialisée s’est traduit par la création d’une Autorité de la concurrence aux pouvoirs proche d’une juridiction. S’expliquant par une forte prégnance du fait économique dans l’analyse des pratiques anticoncurrentielles, à l’avantage notamment de l’Autorité de la concurrence, le rôle du juge a pourtant évolué au fil des ans. Finalement, est apparu un clivage entre une action publique qui vise à prévenir, à dissuader et à sanctionner les comportements anticoncurrentiels et une action privée qui favorise la réparation d’un préjudice causé aux victimes de pratiques anticoncurrentielles. Il en résulte un rôle différencié dans l’application du droit de la concurrence qui renouvelle la réflexion sur la définition d’un juge du droit de la concurrence
Keywords: Autorité de la concurrence; Commerce (réglementation); Competencia; Competition law; Concurrence; Droit; France; Infractions économiques et financières; Judge; Juge; Juges

The interface between competition and intellectual property law : finding common ground and resolving the tensions between these areas of law from a South African perspective - Dercksen, Juletha-Marie (Stellenbosch University, 2023)
Competition law and intellectual property law share the objective of incentivising innovation. However, this objective is achieved in different ways, which, at times, can create tension between the two areas of law. It is imperative that this tension at the interface of competition law and intellectual property law is resolved in a manner that encourages innovation. Issues regarding the licensing of intellectual property, Standard Essential Patents, pay-for-delay agreements and no-challenge clauses are instances where the tension between competition law and intellectual property law is especially prevalent. These instances will be discussed in detail, and what is learnt from how the European Union and Australia handles it, will be applied to South Africa. The European Union, Australia and South Africa have different ways of dealing with situations where the exercise of intellectual property rights has an effect on competition. The European Union has block exemptions, which contains “safe havens” for conduct in specific circumstances. The block exemptions are often accompanied by guidelines, providing firms and individuals with greater detail in order to self-assess their compliance with the exemption. Australia has authorisation, notification and class exemption procedures. Firms can apply to the Australian Competition and Consumer Commission to authorise conduct that might potentially breach the Competition and Consumer Act 2010. Exemptions may also be granted more broadly by the Australian Competition and Consumer Commission in terms of the class exemption procedures. In South Africa, the law concerning the interface between competition law and intellectual property is still in its infancy, and a lot can be learned from jurisdictions like the European Union and Australia regarding the most efficient way to handle this tension. Currently, the Competition Act 89 of 1998 in South Africa contains Section 10(4), the intellectual property exemption clause. A firm can apply to the Competition Commission for an intellectual property exemption from the application of Chapter 2 of the Competition Act “to an agreement or practice, or a category of agreements or practices” which pertains to the exercise of intellectual property rights. However, it is submitted that Section 10(4), by itself, is not the most efficient mechanism to resolve the tension that arises at the interface of competition law and intellectual property law in a way that incentivises innovation. It is proposed that the exemption provision can be made more effective if it is properly applied in conjunction with class exemptions and guidelines.
Keywords: Antitrust law; Australia; Competencia; Competition Act, 1998; Competition law; Conflict of laws; Intellectual property; South Africa; Trade regulation

The goals of competition law for merger analysis in developing jurisdictions : a critical appraisal of merger analysis under Kenyan competition law - Njako, Priscilla Mumbua (University of Pretoria, 2023)
This thesis considers whether jurisdictional exigencies should influence competition law enforcement, with a specific focus on merger analysis. It examines various approaches and schools of thought regarding the goals of competition law and how these play out within jurisdictional parameters. The history of enforcement of American antitrust is scrutinised to establish the nature of the interplay between greater economic policy direction and the goals of competition law. The study also explores the issue of convergence and whether developing jurisdictions should align their competition law to that of developed jurisdictions with mature competition law.
Keywords: American antitrust; Competencia; Competition law; Concurrence (droit); Kenya; Merger analysis